Changes in the Oral Cavity, the State of Periodontal Tissues in Smokers (Eurasian Medical Research Periodical, 2023)
It is no longer news that tobacco smoking causes physical and psychological dependence and is a serious danger to human health. In addition to nicotine, cigarette smoke contains nearly 4,000 different compounds, many of which cause cancer. Tobacco smoking is responsible for 90% of deaths from lung cancer, 75% from bronchial cancer and 25% from coronary heart disease. A lot of people talk about the dangers of smoking. The main focus is on the carcinogenic effect on the lungs and the increased risk of cardiovascular disease. Everyone is afraid of these life-threatening diseases. But smoking has a huge harmful effect on the teeth as well. Constant smoking leads to a gradual darkening of tooth enamel. The high temperature of the smoke alternates with cooled inhaled air, which leads to the formation of microcracks on the surface of the enamel. Components of tobacco smoke accumulate in the enamel, causing darkening of the teeth. The severity and persistence of staining depends on various factors, including the frequency of tobacco smoking. But unattractive appearance is far from the only oral problem caused by smoking.